Serological and molecular characterization of HBV infection with HBsAg reactive and HBV DNA non-reactive - Chunxiang LI; Xiaohan GUO; Peng SUN; Xiaochun LIU; Dan LIU; Lei ZHOU; Liang ZANG; Daniel Candotti; Xuelian DENG (Zhongguo shuxue zazhi, 2022)
Objective To investigate the serological and molecular characteristics of HBsAg+ /HBV DNA non-reactive (NR) infections. Methods Samples tested as HBsAg+ and HBV DNA NR were confirmed by individual NAT repeat testing, viral particle concentration by PEG precipitation combined with in-house nested PCR and real-time quantitative PCR, anti-HBc testing, and HBsAg quantification. HBV sequences were compared with those from donors with chronic and occult infection as controls. Results A total of 792 195 samples were screened between January 2011 and December 2020, of which 53 (1: 14 947) were confirmed HBsAg+ /HBV DNA NR. HBV DNA was detected further in five (9.4%) samples; three S sequences and four Pre Core/Core sequences were obtained. Unique amino acid substitutions (P130T, P135Q/S, R151Q, G153S and S155F) were found in the Core protein that may affect virus packaging and replication. Conclusion Extremely low HBV DNA level was detected in plasmas of HBsAg+ /HBV DNA NR donors. Barely detectable HBV DNA might be associated with unusual mutations in the Pre Core/Core protein affecting viral replication. More sensitive HBV DNA and/or HBsAg assays may be considered to further reduce the potential HBV transfusion-transmission residual risk.